Peranan Madrasah Diniyah Dalam Meningkatkan Akhlak Di Madrasah Diniyah Baitullah Waru Sidoarjo - Andini Fitria Rahmadani; Wahyu Eko Pujianto (Universitas 45 Surabaya, 2023)
Madrasah Diniyah is one of the learning institutions, recognized as having a sizable contribution in raising and improving the world of learning. Madrasah Diniyah is also believed to be an alternative for solving various learning problems that are currently occurring. The role of Madrasah Diniyah in building the character of students in the current era of globalization is very significant, related to various problems that are currently in the public spotlight both in terms of culture, learning and so on. The topic of research this time is very important to discuss in order to be able to provide information, insight so that it can be considered by all Indonesian people, especially the people of Sidoarjo Regency so that they can enter non-formal schools in Madrasah Diniyah so that their sons and daughters can achieve optimal learning.